2016
DOI: 10.3390/w8090365
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Four Full-Scale Artificially Aerated Horizontal Flow Constructed Wetlands for Domestic Wastewater Treatment

Abstract: A comparison of the performance of four full-scale aerated horizontal flow constructed wetlands was conducted to determine the efficacy of the technology on sites receiving high and variable ammonia loading rates not yet reported in the literature. Performance was assessed in terms of ammonia and solids removal, hydraulic conductivity and mixing patterns. The capability of systems to produce ammonium effluent concentrations <3 mgNH 4 + -N/L was observed across all sites in systems receiving variable loadings b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In recent decades, use of active aeration (e.g., an air pump connected to a subsurface network of air distribution pipes) has been applied to HF wetlands (Wallace, 2001;Higgins, 2003;Ouellet-Plamondon et al, 2006;Maltais-Landry et al, 2009;Butterworth et al, 2016) as well as saturated VF wetlands (Murphy and Cooper, 2011;Wallace and Liner, 2011;van Oirschot et al, 2015). In the UK, over 40 tertiary treatment HF wetlands have been successfully retrofitted with aeration systems to increase treatment capacity and extend asset life (Murphy et al, 2016).…”
Section: Aerationmentioning
confidence: 99%
“…In recent decades, use of active aeration (e.g., an air pump connected to a subsurface network of air distribution pipes) has been applied to HF wetlands (Wallace, 2001;Higgins, 2003;Ouellet-Plamondon et al, 2006;Maltais-Landry et al, 2009;Butterworth et al, 2016) as well as saturated VF wetlands (Murphy and Cooper, 2011;Wallace and Liner, 2011;van Oirschot et al, 2015). In the UK, over 40 tertiary treatment HF wetlands have been successfully retrofitted with aeration systems to increase treatment capacity and extend asset life (Murphy et al, 2016).…”
Section: Aerationmentioning
confidence: 99%
“…Due to usually long retention times, HSSF-CWs can provide a reliable secondary level of treatment, and it has been shown that they are effective in removing total suspended solids (TSS) and organic matter (OM), and also allow the removal of nutrients, although with variable and lower efficiencies [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, AA improves the resistance of CWs to the fluctuating influent loads [13] and intensifies mineralization of solids to prevent clogging of the system, and thus increases the lifespan of CWs [13,21]. Studies on AA in CWs have been conducted mostly in short-term laboratory-scale and pilot scale experiments, but very few experiments focused on long-term full-scale systems or its integration in hybrid CWs [7,13,22]. Moreover, seasonal variations of nutrient removal in aerated full-scale hybrid systems still remain unclear.…”
Section: Introductionmentioning
confidence: 99%